Renewable Energy In Ukraine: Towards National Eco-Management - Fedorova, Katerina (Journal of Sustainable Development Law and Policy, 2025)
The national energy security and independence issue is currently the most important problem in Ukraine. Continuous political games around traditional energy import sources exhaust the Ukrainian economy and lead to a systemic crisis. Ukraine has a huge natural potential for the development of green economy, but sustainable development in Ukraine is still at the initial stage of its evolution. Certainly, the transition to renewable energy technologies will be an effective solution to the key energy, environmental, social and political crises in Ukraine. Thus, the main attention of the author is focused on the renewable energy sources, including solar, wind, hydro, biomass and geothermal. It is emphasized that Ukraine has its national production of technical equipment for each of these areas of renewable energy. Along with alternative energy development issues, the author opens a wide panorama of current political, economic, social and security problems in Ukraine, which are deeply interdependent. The author argues that at its current level of development, Ukraine needs a comprehensive update of national ecomanagement strategy and a rational use of the potential natural programme. This will help the country to overcome the crisis permanently, transit from being a consumerist economic model towards an environmentally sustainable economic development and to integrate completely into Euro-Atlantic structures.